P400 A study of the ecology, evolution and resistance mechanism of Candida auris at a tertiary care center in North India. (20th September 2022) - Gupta, Sonakshi; Xess, Immaculata; Singh, Gagandeep; CS, Saumya; Iram, Azka; Soneja, Manish
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Aim: To study the ecology, evolution, and resistance mechanism of Candida auris, using samples from patients, healthcare workers, hospital and environmental niches, using amplified fragment length polymorphism (AFLP) and antifungal susceptibility testing (AFST). Methods: A total of 720 samples were screened for C. auris, including clinical samples from patients (tissue, body fluids), surveillance samples from patients (axillar/groin swabs), swabs and water samples from environmental locations and objects, surface swabs from hospital locations, and screening samples from healthcare personnel for hand carriage of C. auris . Samples were cultured on Sabouraud Dextrose agar (SDA) and CHROMagar. Colonies morphologically suggestive of C. auris were identified by Matrix Assisted Laser Desorption-Time of Flight (MALDI-TOF) and isolates were subjected to antifungal susceptibility testing (AFST) by broth micro-dilution method. DNA was extracted for analysis by amplified fragment length polymorphism (AFLP) and cluster analysis. The amplicons were subjected to capillary electrophoresis and fluorescent amplified length polymorphism (FALP) for the generation of a heat map and dendrogram to evaluate single nucleotide polymorphisms and single nucleotide variations (SNPs and SNVs). Results: Out of 720 samples, C. auris was isolated and identified by MALDI-TOF from 50, including 37 from routine patient samples, 12/674 axillar/groin surveillance swabs, and 1/66 samples from hands of healthcare workers. C. auris was not isolated from any environmental samples or hospital surfaces. AFST revealed high overall rates of resistance to three important antifungal drugs−93.22%, 38.98%, and 52.54% of isolates were resistant to fluconazole, voriconazole, and amphotericin B respectively. Resistance to echinocandins was lower−1.81% of isolates were resistant to caspofungin, and micafungin. Additionally, 18 isolates showed only intermediate sensitivity to both voriconazole and caspofungin. The highest rates of resistance to amphotericin B, and azoles were observed in isolates from blood (62.5% of isolates) and axillar/groin swabs (44.5% of isolates) respectively. Resistance to caspofungin was seen in 14.28% of isolates from both groups. AFLP and capillary electrophoresis of extracted DNA revealed 188 variations in the range of 300-662 nucleotides. A total of 10 samples had no change in the nucleotides and were labeled as 'constant'. The dendrograms generated by bioinformatic analysis of FALP results yielded two different clusters provisionally designated as cluster I and cluster II. Cluster I could be further distinguished into sub-cluster Ia and sub-cluster Ib, indicating further variations. Conclusions: Candida auris is a pathogen of emerging importance in our center, with significant levels of resistance to several important antifungal drugs. Incidence of both the pathogen and antifungal drug resistance was observed in samples collected from patients, but not from the hospital or environment, and minimally from healthcare personnel. This suggests that the source of most C. auris infections is colonizers from the patient rather than environmental sources or healthcare workers, and infection control measures should be tailored accordingly.